Competition and food restriction effects on oxidative stress in judo - Finaud, J.; Degoutte, F.; Scislowski, V.; Rouveix, M.; Durand, D.; Filaire, E. (International Journal of Sports Medicine, 2006)
We examined the effects of weight loss induced by restricting energy and fluid intake on antioxidant status and oxidative stress of judo athletes. Twenty male judoka were randomly assigned to one of two groups (Group A: called diet, n = 10; height 174.8 ± 1.9 cm, body weight 75.9 ± 3.1 kg; they were asked to lose ~ 5 % of their body weight through self-determined means during the week before the competition; Group B: called control, n = 10; height 176.4 ± 1.1 cm, body weight 73.3 ± 6.3 kg maintained their body weight during the week before the competition). A battery of tests was performed during a baseline period (T1) on the morning of a simulated competition (T2) and 10 minutes after the end of the competition (T3). These tests included assessment for body composition, determination of lag phase (Lp) before free radical induced oxidation, maximum rate of oxidation (Rmax) during the propagating chain reaction and maximum amount of conjugated dienes (CDmax) accumulated after the propagation phase, and lipidic profile. Uric acid concentrations were also evaluated in plasma. Dietary data were collected using a 7-day diet record. We noted that the athletes followed a low carbohydrate diet whatever the period of the investigation. Concerning antioxidant nutrients, we can notice that mean nutritional intakes are in the normal range values for vitamin A, C and E at T1 and T2. Rapid weight loss induced a significant increase in Lp values (p < 0.05) and uric acid concentrations without alterations in oxidative stress. Our data also showed that the competition induced the same changes of oxidative-antioxidant status whatever the dietary intake during the seven days before the competition. Moreover, the effect of the competition on the antioxidant and oxidant parameters was more pronounced than the diet. Theses results could be linked to the food containing a large proportion of PUFA and a relative low proportion of carbohydrates.